Achieving the Millennium Development Goal for Under-five Mortality in Bangladesh: Current Status and Lessons for Issues and Challenges for Further Improvements (Journal of Health, Population and Nutrition, 2011)
The study assessed the achievements in, critically reviewed the relevant issues of, and put forward recommendations for achieving the target of the Millennium Development Goal relating to mortality of children aged less than five years (under-five mortality) in Bangladesh within 2015. To materialize the study objectives, a thorough literature review was done. Mortality of under-five children and infants decreased respectively to 65 from 151 and to 52 from 94 per 1,000 livebirths during 1990-2006. The immunization coverage increased from 54% to 81.9% during the same period. The projection shows that Bangladesh will achieve targeted reduction in under-five mortality and infant mortality within the time limit, except immunization coverage. Neonatal mortality contributed to the majority of childhood deaths. Contribution of neonatal mortality to child mortality was the highest. There were remarkable differences in child mortality by sex, division, and residence. To progress further for achieving the target of MDG relating to child mortality, some issues, such as lower use of maternal healthcare services, hazardous environmental effects on childhood illness, high malnutrition among children, shorter duration of exclusive breastfeeding practices, various child injuries leading to death, low healthcare-use of children, probable future threat of financial shortage, and strategies lacking area-wise focus on child mortality, need to be considered. Without these, the achievement of MDG relating to child mortality may not be possible within 2015. Key words: Achievements; Child mortality; Infant mortality; Millennium Development Goals; Review literature; Bangladesh DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7813 J HEALTH POPUL NUTR 2011 Apr;29(2):92-102